Subunit architecture of multimeric complexes isolated directly from cells. - Hernández, H; Dziembowski, A; Taverner, T; Séraphin, B; Robinson, C (2006)
Recent developments in purification strategies, together with mass spectrometry (MS)-based proteomics, have identified numerous in vivo protein complexes and suggest the existence of many others. Standard proteomics techniques are, however, unable to describe the overall stoichiometry, subunit interactions and organization of these assemblies, because many are heterogeneous, are present at relatively low cellular abundance and are frequently difficult to isolate. We combine two existing methodologies to tackle these challenges: tandem affinity purification to isolate sufficient quantities of highly pure native complexes, and MS of the intact assemblies and subcomplexes to determine their structural organization. We optimized our protocol with two protein assemblies from Saccharomyces cerevisiae (scavenger decapping and nuclear cap-binding complexes), establishing subunit stoichiometry and identifying substoichiometric binding. We then targeted the yeast exosome, a nuclease with ten different subunits, and found that by generating subcomplexes, a three-dimensional interaction map could be derived, demonstrating the utility of our approach for large, heterogeneous cellular complexes.